Application of author's and unoficient methods of physical therapy for chronic obstructive pulmonary disease - Savchenko, V. M. (Journal of Education, Health and Sport, 2017)
The purpose of the study is to establish the role of copyright and informal methods of physical therapy in chronic obstructive pulmonary disease (COPD) according to the literature.Materials and methods. Literary sources over the past 10 years, selected from the electronic databases of the National Library of Ukraine named V.I. Vernadsky, Russian scientific electronic library "eLibrary", Web of Science, PubMed, PEDro.Results. In COPD, not only officially recognized methods of physical therapy, but also informal ones are used to improve the clinical condition, respiratory function, daily physical activity and quality of life of patients. For this purpose, over the past 10 years, A.N. Strelnikova, and abroad – Pilates gymnastics, exercises of Yoga, Tai Chi, Qigong, singing and yoga of laughter. However, the data on the effectiveness of the methods used are contradictory and inconclusive due to the poor quality of the research.Findings. Currently there are no convincing data on the effectiveness of copyright, traditional Oriental and other unofficial methods of physical therapy in COPD.